The sacrifice in the Holy Qur'an Interpretive Analytical Study - Abdul Hussain Rashid Maarij Al Shuwaili ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
he Almighty said in his book: 'This is insight from your Lord, guidance and mercy' Al-A'raf (203), and in this guidance there is life for people, and this light is not for looking, but for life and behavior.Yes, reason, instinct and knowledge cannot be dispensed with, but it is wrong to imagine that thanks to them, the sacred revelation is dispensed with.  If we are separated from the guidance of revelation, then we are not free from dissolution. And this is what we see in the Islamic society after they discarded the Book of God .In this research we deal withone of the vocabulary of the Qur’an (the sacrifice) is an analytical study through research, on three paragraphs: (the sacrifice in language and idiomatically, the analysis of the Qur’anic texts and the reasons for the revelation, the sacrifice in Islamic thought.